Synthesis and Characterization of Polyurethanes of Isophorone Diisocyanate Containing Bis(azo) and Bis(o-Nitrobenzyl) Chromophores in the Main Chain - Sudheesh Kumar, K. (Asian Journal of Chemistry, 2011)
A series of photosensitive polyurethanes containing bis(azo) and bis(o-nitrobenzyl) groups were synthesized by polyaddition reactions of diols such as bis(4-hydroxyphenylazo)-2,2'- dinitrodiphenylmethane, 4-hydroxy-3-methylphenylazo-4'-hydroxy-phenylazo-2,2'-dinitrodiphenylmethane and bis(4-hydroxy-3-methylphenylazo)-2,2'-dinitro-diphenylmethane with isophorone diisocyanate, in dimethyl acetamide in presence of di-n-butyltin dilaurate as catalyst. All of them were characterized by IR, UV-vis, 1H and 13C NMR spectra and also by differential scanning calorimetry and gel permeation chromatography.